2020
DOI: 10.1002/lsm.23244
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of Picosecond Laser in Dermatology: Evidence and Recommendations

Abstract: Background and Objectives The use of picosecond laser in dermatology was originally focused on optimizing the removal of unwanted tattoos. Subsequent advances in this technology have broadened its clinical indications to include treatment of benign pigmented lesions, photodamage, melasma, and scar revision. In this systematic review, evidence‐based recommendations are developed for the use of picosecond laser in dermatology. Study Design/Materials and Methods A comprehensive search of the English language lite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
126
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(130 citation statements)
references
References 93 publications
3
126
0
1
Order By: Relevance
“…Thermal damage seems to be the greatest drawback of conventional Q‐switched laser treatment for patients with melasma, and likely the cause of the high incidence of PIH after treatment. A recent systematic review by Wu et al [10] reported the use of picosecond lasers for melasma in one case series, one prospective open‐label trial, four prospective, randomized split‐face trials, and one randomized controlled trial and concluded that this modality may be offered as an adjunctive treatment in patients with moderate to severe melasma. However, it was also mentioned that the safety and efficacy of fractionated versus nonfractionated delivery is yet to be confirmed.…”
Section: Discussionmentioning
confidence: 99%
“…Thermal damage seems to be the greatest drawback of conventional Q‐switched laser treatment for patients with melasma, and likely the cause of the high incidence of PIH after treatment. A recent systematic review by Wu et al [10] reported the use of picosecond lasers for melasma in one case series, one prospective open‐label trial, four prospective, randomized split‐face trials, and one randomized controlled trial and concluded that this modality may be offered as an adjunctive treatment in patients with moderate to severe melasma. However, it was also mentioned that the safety and efficacy of fractionated versus nonfractionated delivery is yet to be confirmed.…”
Section: Discussionmentioning
confidence: 99%
“…In order to achieve similar results, QS lasers on average required far greater fluence than PS lasers and consequently higher risk of side effects. In addition, they recommended that PS lasers to be used as the gold standard for laser tattoo removal of any color with level of evidence of 1A 41 …”
Section: Recent Development and Technique Modificationsmentioning
confidence: 99%
“…Novel technologies like picosecond lasers, have been used successfully in the treatment of hypertrophic scars revealing histological changes like collagen fiber reconfiguration and reduction of epidermal thickness in hypertrophic scars 60 but evidence remains scarce, considered as level 3c 61 …”
Section: Overview Of Fractional Lasersmentioning
confidence: 99%